(untitled) (Doctor Virtualis, 2023)
The attempts made within the Thomist tradition to identify the official doctrine of analogy elaborated by Thomas Aquinas had to deal with the various distinctions drawn by Aquinas in his writings. In particular, the great importance given to the agreement of proportionality in the Quaestiones disputatae de veritate has elicited a long debate, in which those who consider such a solution as the authentic doctrine are opposed to those who see it merely as a temporary stage of an evolution which could be observed in Thomas’s works. The aim of this essay is to present some textual data that contribute to clarify the transition from the analogy as conceived in the Scriptum super Sententiis to that of the De veritate, a transition closely related to the heuristic function of analogy.